2019
DOI: 10.1002/jbt.22375
|View full text |Cite
|
Sign up to set email alerts
|

LOX‐1: Its cytotopographical variance and disease stress

Abstract: Lectin‐like oxidized low‐density lipoprotein receptor‐1 (LOX‐1) is a canonical receptor for oxidized LDL (oxLDL) among the known modified LDL particles. Topographical variance on LOX‐1 expression in different cell types and its influence on the atherogenic potential of the particular cell type is the main focus of this review. Characteristic features of LOX‐1 on the atherogenic potential of aortic endothelial cells, macrophages, platelets, and vascular smooth muscle cells have been discussed. Nonspecificity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 104 publications
(134 reference statements)
0
3
0
Order By: Relevance
“…As all statins can disrupt the binding of ox-LDL to the C-type lectin-like recognition domain of LOX-1, they all have the same effects of alleviating ox-LDL-induced endothelial ferroptosis (10). Previous studies have demonstrated that ox-LDL does not interact with xCT and GPx4 directly, but that it rather acts via LOX-1 (34)(35)(36). Similarly, all tested statins (atorvastatin, fluvastatin, lovastatin, pitavastatin and pravastatin) did not directly interact with xCT and GPx4 to improve ferroptosis (10), but protected endothelial cells from ferroptosis by disrupting the interaction of ox-LDL with LOX-1.…”
Section: Discussionmentioning
confidence: 99%
“…As all statins can disrupt the binding of ox-LDL to the C-type lectin-like recognition domain of LOX-1, they all have the same effects of alleviating ox-LDL-induced endothelial ferroptosis (10). Previous studies have demonstrated that ox-LDL does not interact with xCT and GPx4 directly, but that it rather acts via LOX-1 (34)(35)(36). Similarly, all tested statins (atorvastatin, fluvastatin, lovastatin, pitavastatin and pravastatin) did not directly interact with xCT and GPx4 to improve ferroptosis (10), but protected endothelial cells from ferroptosis by disrupting the interaction of ox-LDL with LOX-1.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, VSMCs in individuals with T2D exhibit increased expression of the antiapoptotic protein Bcl-2, leading to resistance to cell death, enhanced proliferation, and a thicker media layer [ 110 ]. Prolonged exposure to elevated glucose levels induces oxidative stress in vascular cells, a crucial factor in the progression of atherosclerosis [ 111 , 112 , 113 , 114 ].…”
Section: Vascular Smooth Muscle Cell Phenotype Switching In Diseasementioning
confidence: 99%
“…Recent research has shown that gallic acid has anti-inflammatory effects and inhibits LOX-1 production [ 152 ]. Hydroxymethylglutaryl-CoA-reductase (HMG-CoA-reductase) inhibitors, namely, statins, reduce cardiovascular mortality by decreasing cholesterol as well as by non-lipid-related actions [ 153 ].…”
Section: Inhibition-strategies For Lox-1mentioning
confidence: 99%